2007
DOI: 10.3390/12030423
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Antioxidants Identified by ESI-MS from Yerba Maté (Ilex paraguariensis) and Green Tea (Camelia sinensis) Extracts

Abstract: Aqueous extracts of green yerba maté (Ilex paraguariensis) and green tea (Camellia sinensis) are good sources of phenolic antioxidants, as already described in the literature. The subject of this study were organic extracts from yerba maté, both green and roasted, and from green tea. Their phenolic profiles were characterized by direct infusion electrospray insertion mass spectrometry (ESI-MS) and their free radical scavenging activity was determined by the DPPH assay. Organic extracts containing phenolic anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
140
1
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(173 citation statements)
references
References 34 publications
21
140
1
11
Order By: Relevance
“…This decrease on phenolic compounds can reduce antioxidant activity in the oxidized leaves . Indeed, the relationship between phenolic content and antioxidant activity is widely described in literature for different plants (Nunes, 2007;Heck and Mejia, 2007;Bastos et al, 2007).…”
Section: Antioxidant Activity Of I Paraguariensis St Hil In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease on phenolic compounds can reduce antioxidant activity in the oxidized leaves . Indeed, the relationship between phenolic content and antioxidant activity is widely described in literature for different plants (Nunes, 2007;Heck and Mejia, 2007;Bastos et al, 2007).…”
Section: Antioxidant Activity Of I Paraguariensis St Hil In Vivomentioning
confidence: 99%
“…The yerba-mate fits in this context, due to the numerous benefits to health it provides, such as hypocholesterolemic and hepatoprotective activity (Filip and Ferraro, 2003;Açari et al, 2011); central nervous system stimulation; diuretic action (Castaldelli et al, 2011), inhibition of neoplastic cells proliferation (Mejía et al, 2010); and antioxidant activity, preventing damages caused by free radicals (Bastos et al, 2007). Studies showed that among ten plant species used as teas, the yerba-mate was one that showed the highest antioxidant capacity (Asolini et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that compounds found in mate tea, mainly polyphenols, have antioxidant, antiinflammatory, immunomodulatory and anticancer effects 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…ESI-MS employs little sample preparation and gives immediate compositional information for ESI-ionizable compounds. It has been very efficient for fingerprinting complex mixtures such as that of soybean extracts, 11 tea, 12 spices, 13 vegetable oil 14 and more recently, it has been applied to investigate the differences between Arabica and Robusta defective green coffees. 15 We report herein the ESI-MS fingerprinting of the methanolic extracts of Arabica coffees in the positive and negative ion modes, ESI(+)-MS and ESI(-)-MS, respectively.…”
Section: Introductionmentioning
confidence: 99%